Perjalanan Hidup dan Perkembangan Usaha Rumah Makan H. Rusdi Syafri - Amalia, Dinda Putri; Fatimah, Siti (Jurnal Kronologi, 2025)
This research is a Thematic Biography that examines the life journey of H. Rusdi Syafri from dishwasher to restaurant entrepreneur. This study addresses two research questions: (1) What was H. Rusdi Syafri's life like before becoming an entrepreneur? and (2) How did his business develop from 1992-2024? The method used is historical research, which includes: (1) Heuristics for collecting primary data (interviews) and secondary data (observations and documents), (2) Source Criticism with external and internal criticism, (3) Interpretation of historical facts, and (4) Historiography for scientific writing. The results show that H. Rusdi Syafri, born on March 26, 1965, in Nagari Sumpur, began his career as a dishwasher after graduating from elementary school. In 1989, he opened a small restaurant named Fajar Baru, and in 1991, he founded Taman Selera Restaurant in Indramayu. Taman Selera grew rapidly, employing 300 employees, partnering with 10 bus operators, and serving around 40 buses daily. With an area of 4 hectares, Taman Selera became one of the largest restaurants in Indramayu. H. Rusdi Syafri's story inspires many through his contributions in creating jobs and helping the local community as well as his hometown of Nagari